Organizational and Economical Methods of Efficiency of Gas Mains Operation Join-Stock Company “Beltransgas” - V. V. Maiorov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In this article the experience of JSC ”Beltransgas” has been generalized, and the main ways of reliabilty increasing of gas supply systems in the Republic of Belarus are considered. The main attention is paid to the energy-saving technologies owing to the usage of compressor-transfer device’s potential and modern methods and materials for insulation and re-insulation of steel pipes of big diameter to provide conditions for long-term service.